Music in religious cults of the ancient Near East - Smith, John Arthur, 1946- author.
1 online resource (221 pages)
Keywords: Music in Religious Cults of the Ancient Near East presents the first extended discussion of the relationship between music and cultic worship in ancient western Asia. The book covers ancient Israel and Judah, the Levant, Anatolia, Mesopotamia, Elam, and ancient Egypt, focusing on the period from approximately 3000 BCE to around 586 BCE. This wide-ranging book brings together insights from ancient archaeological, iconographic, written, and musical sources, as well as from modern scholarship. Through careful analysis, comparison, and evaluation of those sources, the author builds a picture of a world where religious culture was predominant and where music was intrinsic to common cultic activity.